Modified Lung Ultrasound Score for Assessing and Monitoring Pulmonary Aeration - Mongodi, Silvia; Bouhemad, Bélaïd; Orlando, Anita; Stella, Andrea; Tavazzi, Guido; Via, Gabriele; Iotti, Giorgio Antonio; Braschi, Antonio; Mojoli, Francesco (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose Lung Ultrasound Score (LUSS) is a useful tool for lung aeration assessment but presents two theoretical limitations. First, standard LUSS is based on longitudinal scan and detection of number/coalescence of B lines. In the longitudinal scan pleura visualization is limited by intercostal space width. Moreover, coalescence of B lines to define severe loss of aeration is not suitable for non-homogeneous lung pathologies where focal coalescence is possible. We therefore compared longitudinal vs. transversal scan and also cLUSS (standard coalescence-based LUSS) vs. qLUSS (quantitative LUSS based on % of involved pleura). Materials and methods 38 ICU patients were examined in 12 thoracic areas in longitudinal and transversal scan. B lines (number, coalescence), subpleural consolidations (SP), pleural length and pleural involvement (> or ≤ 50 %) were assessed. cLUSS and qLUSS were computed in longitudinal and transversal scan. Results Transversal scan visualized wider (3.9 [IQR 3.8 – 3.9] vs 2.0 [1.6 – 2.5] cm, p < 0.0001) and more constant (variance 0.02 vs 0.34 cm, p < 0.0001) pleural length, more B lines (70 vs 59 % of scans, p < 0.0001), coalescence (39 vs 28 %, p < 0.0001) and SP (22 vs 14 %, p < 0.0001) compared to longitudinal scan. Pleural involvement > 50 % was observed in 17 % and coalescence in 33 % of cases. Focal coalescence accounted for 52 % of cases of coalescence. qLUSS-transv generated a different distribution of aeration scores compared to cLUSS-long (p < 0.0001).Conclusion In unselected ICU patients, variability of pleural length in longitudinal scans is high and focal coalescence is frequent. Transversal scan and quantification of pleural involvement are simple measures to overcome these limitations of LUSS.
Keywords: lung ultrasound; lung aeration assessment; lung ultrasound score; lung aeration monitoring